It's never too late to improvise: The impact of theatre improvisation on elderly population. Issue 2 (15th March 2023) - Bassis, Daniella; Rybko, Judit; Maor, Rotem
ABSTRACT: Despite the availability of improvisational theater training in different settings, studies that assess its effectiveness as a means for enhancing cognitive training for older adults are scarce. This study examines the influence of short theater improvisation exercises on the cognitive flexibility of cognitively-healthy older adults, and their influence on the four core components of improvisation (i.e., spontaneity, flow, creativity, playfulness). The study also examines the correlation between an improvement in these four key agents and an improvement in cognitive flexibility among older adults. This quantitative empirical study was conducted in retirement homes and daycare centers in Israel. A total of 45 participants took part in this study, all in good physical health and with age-appropriate cognitive abilities. The participants were divided into five research groups; each group met twice a week for a one-hour improvisation session over a six-week period. The data was collected through five questionnaires that were completed at four points of time (before, during, and after the workshop). The findings did not indicate a significant effect of the improvisation exercises on the participants' cognitive flexibility, yet they did show improvement in three components of improvisation: spontaneity, flow, playfulness. As such, the findings of this study indicate that despite a normal decline in basic cognitive functioning among older adults, the beneficial effect of improvisation on cognitive flexibility might still occur through spontaneity, playfulness, and flow. In conclusion, short theater improvisation exercises could contribute to various indicators of healthy aging in various settings.